Children and Violence on Television: A Survey of Eau Claire Parents - Barnes-Boldt, Amanda; Neudecker, Erik; Hughes, Jayne; Sims, Judy; Giordano, Joseph (UW Eau Claire Research Day; Leader-Telegram, 1995)
The primary objective of this study, which was accepted for presentation as a poster in UW-Eau Claire’s Student Research Day (May 1-2, 1995), was to gather data concerning a number of areas related to children’s viewing of violent television programming, including: (1) parental monitoring of children’s television viewing; (2) parental evaluations of warnings/advisories, proposed congressional legislation, and “other” potential solutions to violent content on television; (3) the relationship between children’s viewing of television programs containing violent content and children’s display of verbal and nonverbal aggressive behavior; (4) the relationship between children’s viewing of Saturday morning television cartoons and children’s desires to purchase toy weapons; and (5) parental perceptions of the level of violent content on local and/or national television news. Undergraduate students enrolled in a Communication Research Methods course during the Fall Semester 1994 administered questionnaires to a purposive sample of 877 parents and/or legal guardians of children ages 3-12 in Eau Claire, Wisconsin. Of the 877 questionnaires distributed, 351 were returned, achieving a 40% response rate. The UW-Eau Claire Student Research Day poster focused mainly on results related to parental evaluations of warnings/advisories, proposed legislation and “other” potential solutions to violent content on television, including, e.g., (1) a majority of parents and/or guardians ranked “parental control” as their first choice for the most effective solution to violent content on television; (2) “safe harbor” legislation (i.e. the Children’s Protection from Violent Programming Act), which was proposed in 1993 and would have directed the Federal Communications Commission to limit violent programs to time slots when children would be least likely to be viewing, was ranked second; and (3) “warnings/advisories,” which parents and/or legal guardians ranked as third for the most effective solution to violent content on television.
Communication Research Methods students, Amanda (Barnes) Boldt, Erik Neudecker, and Jayne Hughes, designed and presented a poster about the study for UW-Eau Claire’s Student Research Day (May 1-2, 1995). Faculty Advisers/Collaborators: Judy R. Sims and Joseph Giordano. The Eau Claire Leader Telegram published a story about the research, "Research in Teaching: Eau Claire parents control children's viewing habits" (August 27, 1995, 6).
Keywords: Children’s Protection from Violent Programming Act; Congressional legislation related to TV violence; Legislative and non-legislative solutions to TV violence; Parental control; Safe Harbor; Survey questionnaire; Television violence; Television Violence Reduction Through Parental Empowerment Act; V-Chip; Violent content on television; Warnings/Advisories; Wisconsin parents